International Collaboration and Coordination Vietnam’s Energy Transition: The Role of International Partners Through the Just Energy Transition Partnership - Dafa Syachrullah; Shanti Darmastuti (Jurnal Sosial Humaniora, 2026)
Energy transition has become a key global agenda to reduce carbon emissions and lessen dependence on fossil fuels. As a developing country, Vietnam faces significant challenges in meeting rapidly growing energy demand while maintaining its commitment to international climate targets. In this context, multilateral cooperation through the Just Energy Transition Partnership (JETP) with the International Partners Group (IPG) serves as a strategic instrument to support Vietnam’s energy transition process. This study aims to analyze the forms of collaboration and coordination between the Government of Vietnam and international partners in implementing the JETP framework.This research adopts a descriptive qualitative approach. Data were collected through in-depth interviews and document analysis, and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that collaboration and coordination are institutionalized through the establishment of the Resource Mobilisation Plan (RMP) as the main governance framework, national policy reforms in the energy sector, and the development of renewable energy projects supported by financial and technical assistance from the IPG. This cooperation reflects a model of institutionalized multilateralism, in which Vietnam’s national interests and global climate mitigation objectives are aligned through structured policy coordination and inter-actor collaboration.